COMPARISON OF ULTRASONOGRAPHIC ESTIMATION OF FETAL WEIGHT AT TERM AND ITS CORRELATION WITH ACTUAL BIRTH WEIGH (The Research of Medical Science Review, 2025)
BACKGROUND: Accurate estimation of fetal weight at term is critical for planning mode of delivery and reducing maternal and neonatal complications. While clinical methods exist, ultra sonographic estimation using formulas like Hadlock’s is widely used due to its precision and non-invasive nature. However, limited local data are available regarding its accuracy in the Pakistani population.OBJECTIVE: To determine fetal weight by ultrasound at term, compare it with actual birth weight, and assess the correlation between the two.METHODS: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Northwest General Hospital, over six months. A total of 60 term singleton pregnancies (37–42 weeks) were assessed. Fetal weight was estimated using the Hadlock formula on Toshiba Applio 500 ultrasound. Actual birth weight was recorded within one hour of delivery. Data were analyzed using SPSS version 25. Pearson’s correlation coefficient was applied to assess the relationship between estimated and actual weights.RESULTS: The mean ultrasonographic estimated fetal weight was 3123.08 ± 297.7 grams, while the mean actual birth weight was 3134.17 ± 306.9 grams. A strong positive correlation was found between the two (r = 0.965, p < 0.001). About 86.7% of ultrasound estimates were within ±10% of the actual birth weight. No significant variation was found when stratified by age, parity, or BMI.CONCLUSION: Ultrasonographic fetal weight estimation using the Hadlock formula demonstrates high accuracy and a strong correlation with actual birth weight at term. It is a reliable tool for delivery planning. Larger multicenter studies are needed to enhance generalizability